2016
DOI: 10.4081/ija.2016.729
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic and Nutritional Characteristics of Three Buckwheat Cultivars Under Organic Farming in Three Environments of the Garfagnana Mountain District

Abstract: Buckwheat is a crop that has virtually disappeared in Italy, and products are generally imported from Poland and China. Among the alternative crops, suitable for cultivation in marginal areas and mountain foothills, buckwheat is particularly adapted as it is a rustic crop that can be grown without chemical input. Buckwheat is rich in numerous functional components and is, therefore, suitable for the obtaining of health products. The aim of the present research was to evaluate the adaptability of three cultivar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 21 publications
4
11
0
Order By: Relevance
“…The variety Spacinska, originally from Slovakia, provided the worst results, with smaller average height than the other cultivars, indicating a stress during the vegetative growth; these conditions continued even during the ripening of the achenes, leading to a reduced yield and a low weight of seeds per plant. The test weight was medium-low and the weight of the 1000 seeds was medium, respecting also in this case the trend of qualitative characters seen in other tests [14]. As for the locations, this trial confirmed the better adaptation of buckwheat to the climatic conditions of the mountains of central Italy compared to the places at lower altitude, already observed in other tests conducted in Tuscany [14].…”
Section: IVsupporting
confidence: 72%
See 4 more Smart Citations
“…The variety Spacinska, originally from Slovakia, provided the worst results, with smaller average height than the other cultivars, indicating a stress during the vegetative growth; these conditions continued even during the ripening of the achenes, leading to a reduced yield and a low weight of seeds per plant. The test weight was medium-low and the weight of the 1000 seeds was medium, respecting also in this case the trend of qualitative characters seen in other tests [14]. As for the locations, this trial confirmed the better adaptation of buckwheat to the climatic conditions of the mountains of central Italy compared to the places at lower altitude, already observed in other tests conducted in Tuscany [14].…”
Section: IVsupporting
confidence: 72%
“…The test weight was medium-low and the weight of the 1000 seeds was medium, respecting also in this case the trend of qualitative characters seen in other tests [14]. As for the locations, this trial confirmed the better adaptation of buckwheat to the climatic conditions of the mountains of central Italy compared to the places at lower altitude, already observed in other tests conducted in Tuscany [14]. In fact, in the location of Castelluccio were recorded a higher level of coverage, a greater yield per surface unit and an increased production of seeds per plant, and better quality parameters of grain (test weight, weight of 1000 seeds) that indicate an increased filling of the seed.…”
Section: IVmentioning
confidence: 82%
See 3 more Smart Citations